The Importance of Parental Teaching in Shaping Children's Islamic Character: Parents' Perceptions - Romanto, Romanto; Irawan, M Ferry; Zakaria, Abd Razak (Fakultas Tarbiyah - Universitas Nahdlatul Ulama Sunan Giri, 2024)
This study explores the importance of parent teaching practices in shaping Islamic morals in children within the context of a modern society facing moral and ethical challenges. Using a quantitative approach through surveys, data were collected from 100 parents with children aged 5-12 years. The survey instrument was used to identify parent teaching practices, parents' perceptions of their impact, and factors influencing their effectiveness. The survey was then analyzed using percentages to determine the percentage level of parents' opinions. The results indicate that parental involvement, the quality of teaching materials, and consistency in teaching play crucial roles in shaping children's character. The implications of this research emphasize the importance of increasing parental involvement, diversifying teaching methods, and maintaining consistency in Islamic religious education at home. By strengthening parent teaching practices, it is hoped that children will be better equipped to face moral and ethical challenges in modern society.